The Effectiveness of Mediation Services in Resolving Students’ Interpersonal Conflicts: A Systematic Literature Review - Syifa Rahma Isnaeni; Salsabina Aidy Fitriani; Nauroh Salimah Ritonga; Nathania Sevina Sutisna; Cindy Marisa (CERDAS AKADEMIKA NUSANTARA, 2025)
Interpersonal conflicts that occur among students at the high school/vocational high school/Islamic junior high school (SMP) and junior high school levels are difficult to avoid. Guidance and counseling teachers can utilize mediation services, which are expected to enable students to resolve interpersonal conflicts positively. This study aims to determine the effectiveness of mediation services in resolving student interpersonal conflicts through a systematic literature review (SLR) approach. Data were obtained from 172 articles published between 2015 and 2025 using Google Scholar, DOAJ, and other sources. After selecting articles based on inclusion and exclusion criteria, 10 articles were obtained and analyzed using the Prisma method. The results of the analysis indicate that mediation services can effectively address problems that occur between students by fostering empathy, effective communication, and the ability to find solutions together. These findings indicate that mediation services can be an important guidance strategy for guidance and counseling teachers in creating a harmonious, safe, and comfortable school atmosphere for students' social-emotional development.